Holistic Learning through Qurʾānic-Integrated STEM: Innovations in Early Childhood Pedagogy - Nurhayati, Sri; Marhamah; Taufikin; Hani Sholihah; Anissa Tri; Rizky Maemunah; Mohammad Moreb (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study offers a critical investigation into the epistemic and developmental implications of Qurʾānic-integrated STEM pedagogy within holistic early childhood education, as enacted in Indonesian Muslim community-based institutions. Confronting the persistent lacuna between secular STEM initiatives and culturally embedded educational imperatives, the research pursues a nuanced empirical exploration of how educators operationalize Islamic ethical and ontological constructs-rooted in Qurʾānic revelation and Islamic philosophical tradition-within science, technology, engineering, and mathematics curricula. Utilizing a qualitative phenomenological framework, the study sampled thirty-five female educators across institutional variations, employing semi-structured interviews, systematic document analysis, and non-participant classroom observations to triangulate data. Thematic analysis, conducted through iterative coding, elucidated five advanced pedagogical strategies: ritual epistemic framing, scriptural exegesis within scientific dialogue, inquiry-driven didactics, adab-infused socialization, and contemplative synthesis, each representing a locus for epistemological integration between empirical inquiry and spiritual cultivation. Empirical mapping of seven STEM activities revealed intentional alignment with Qurʾānic virtues-syukur (gratitude), amanah (accountability), khalifah (stewardship)-demonstrating their transformative agency across cognitive, psychomotor, spiritual-moral, socio-emotional, and environmental domains of child development. Synthesis of observational and participant narratives substantiated salient advances in learners’ scientific reasoning, metacognitive self-awareness, spiritual affectivity, communal solidarity, and environmental stewardship. These findings decisively extend the scholarly discourse by evidencing that Qurʾānic-integrated STEM environments do not merely impart scientific literacy, but foster learners marked by profound ethical orientation and ecological consciousness.